46. COMPARISON OF THE EFFECTIVENESS OF ANALGESIA DURING AND AFTER PNEUMONECTOMY BETWEEN ERECTOR SPINAE PLANE BLOCK VERSUS EPIDURAL (Vietnam Journal of Community Medicine, 2024)
Objective: The study was conducted to compare the analgesic effect during and after lung resection surgery between continuous erector spinae plane block (ESPB) and epidural anesthesia with 0.125% Ropivacaine combined with 1 mcg/1 ml Fentanyl.Subject and method: A cross-sectional descriptive study included 60 patients with indications for lung resection divided into two groups: 30 patients with pain relief using erector spinae plane block (ESPB) and 30 patients with epidural anesthesia (EA) at Bach Mai Hospital from July 2023 to September 2024.Results: The total amount of fentanyl used during surgery in the ESPB group and the EA group did not differ (p>0.05) (323.20 ± 35.2 and 320.87 ± 36.64 mcg). The amount of morphine consumed after surgery within 24 hours in the ESPB group was 541.67 ± 144.34 (mcg); in the EA group it was 519.35 ± 151.74 (mcg). After 24 hours, the two groups did not need additional morphine. The VAS scores at rest and movement in the ESPB group decreased statistically significantly, similar to the EA group. There was no statistically significant difference in the rate of adverse effects between the two anesthesia groups (p>0.05).Conclusion: ESPB method is effective in increasing intraoperative pain relief and postoperative pain relief equivalent to EA without many serious complications.
Keywords: Erector spinae plane block (ESPB); epidural; pneumonectomy; lobectomy; analgesia